Chronic Prostatitis / Chronic Pelvic Pain Syndrome – problematic common disease. Current knowledge on etiology, diagnosis and treatments - Wojciech Żołyniak; Ziemowit Żaba; Paweł Warzyszak; Róża Małek; Maria Milczek; Izabela Hawranik; Aleksandra Lisowska; Mikołaj Tomasik; Szymon Niski; Mateusz Skrzypek (Quality in Sport, 2022)
Introduction: